Analysis of the Colombian legal system about the foreign commercial societies with reference to private international law - Marín Fuentes, José Luis (Estudios de Derecho, 2007)
This article approachesthe foreign commercialsocieties with seat in Colombia, from the private international law perspective. It shows ambiguities when a valuation is made because they are studied only from the internal point of view, it means, without considering the international law elements that they content. Therefore they should have a different regulation if the purpose is to put under its control and its functioning to the Colombian legal system.